Predicting the impacts of land use/land cover changes on seasonal urban thermal characteristics using machine learning algorithms - Kafy, Abdulla - Al; Saha, Milan; Faisal, Abdullah-Al; Rahaman, Zullyadini A.; Rahman, Muhammad Tauhidur; Liu, Desheng; Fattah, Md. Abdul; Al Rakib, Abdullah; AlDousari, Ahmad E.; Rahaman, Sk Nafiz; Hasan, Md Zakaria; Ahasan, Md Ahasanul Karim (Building and environment, 2022)
Changes in land use/land cover (LULC) and land surface temperatures (LST) contribute significantly to the formation and intensity of urban heat islands (UHI) effects. The urban thermal field variance index (UTFVI) can effectively describe any city's UHI (thermal characteristics) effect. This study aims to assess and predict the seasonal (summer and winter) UTFVI scenario to evaluate the thermal characteristics of Sylhet city, Bangladesh. Landsat 4–5 TM and 8 OLI images from 1995 to 2020 were used to assess the previous status of LULC and UTFVI and predict the future changes for 2025 and 2030 using cellular automata and artificial neural network machine learning algorithms. Prediction results indicate a substantial increase in urban built-up areas by 42% and 44% in 2025 and 2035, followed by reductions in green cover (21% and 22%), bare land (20% and 21%) and water bodies (1%). The rapid expansion of built-up areas will lead to 13 km2 and 14 km2 stronger UTFVI zones in the predicted years. The study provides effective strategies for mitigating the UTFVI effects by avoiding dense infrastructural development, increasing plantation and water bodies, rooftop gardening and using white colour roofs in construction. The findings of this study will allow the urban planners, policymakers and local government to ensure an eco-friendly, inclusive and sustainable urban development through functional modification and replacement of the LULC distribution depending on the present and future circumstances. [Display omitted] •Directional changes of LULC and seasonal UTFVI shift in Sylhet city were analyzed.•Reduction of green cover significantly increase UTFVI effect.•LULC vs UTFVI relationship better explain impacts of different land cover on thermal environment.•Seasonal UTFVI prediction exhibit a gradual decrease in overall thermal characteristics.•Predicted UTFVI vs LULC demonstrated the highest UTFVI concentration in the built-up area.